Determinasi Aglomerasi Industri di Sumatera Utara: Pendekatan Hoover Balassa Index Periode 2018–2023 - Prasetya Kumara, Bima; Azansyah, Azansyah; Apriyanti, Cikit (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to measure the level of agglomeration of large and medium-sized industries in North Sumatra Province using the Hoover Balassa Index and to identify the factors that influence it. The data used is panel data across regions for the period 2018–2023. The index calculation results reveal varying levels of industrial concentration across regions, ranging from very strong to those without comparative advantages. Regression analysis using a fixed effect approach shows that road length has a significant effect on industrial agglomeration, while industrial value added and the Human Development Index (HDI) do not have a significant effect. These findings indicate that infrastructure development, particularly roads, plays an important role in promoting the concentration and growth of industrial zones in North Sumatra Province.